Teacher’s Roles Implemented by an American Lecturer and an Indonesian Lecturer in Teaching Reading Classes - Elsa Septia Herlina; Henny Putri Saking Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This thesis is a qualitative study on teacher's roles implemented by an American lecturer (AL) and an Indonesian lecturer (IL) in the English Department, Petra Christian University when they taught Reading classes. The objectives of this study are to find out the teacher's roles of both lecturers and their differences and similarities. This study used Harmer's theory on teacher's roles (2015). The data were collected twice for each lecturer. The findings show that the lecturers applied the teacher's roles: controller, monitor, prompter, editor, resource, and organizer. There were roles of evidence gatherer, tutor, and facilitator that were not implemented by both lecturers. This study also found multiple roles in one utterance. For the difference, only AL played the role of prompter when teaching. In conclusion, the topic of reading passages might affect the teacher’s roles implemented by AL and IL.